Internal travel and risk of dengue transmission in Colombia - Chaparro, Pablo Enrique (2014)
Human behavior plays a key role in the dynamics of dengue transmission. However, research on the relationship between human movement and dengue transmission within endemic countries is limited. From January 2008 to December 2011, the authors of this study conducted a retrospective analysis of imported dengue infections in Bogotá, Colombia. Bogotá is a vector-transmission-free city that is also the capital district and most populated municipality in Colombia. The study revealed that 1) Bogotá inhabitants acquired dengue infection in diverse localities throughout the country but the largest proportion of cases (35.6%) were contracted at popular tourist destinations in dengue-endemic areas near Bogotá (<200-km radius from city limits), and 2) the number of imported dengue cases increased after major holidays, a transmission pattern not seen in dengue-endemic areas, where disease incidence correlates with rainy periods. It is therefore recommended that physicians consider the effect of travel when diagnosing their patients' illnesses, especially outside dengue-endemic areas where diagnosis of the disease can be challenging due to its nonspecific symptoms. The study also showed that analysis of dengue cases imported to regions free of vector transmission can generate an evidence-based model for characterizing the impact of human movement on the spread of diseases like dengue in countries where they are endemic.